Style of life and well-being of students in the health area - Isabely, Isabely Ribeiro (2017)
The aim of this study was to identify the lifestyle and well-being of undergraduate students in a public educational institution. It is a cross-sectional study carried out with 70 students of health courses at a public higher education institution located in the state of Minas Gerais, in the southeastern region of Brazil. A questionnaire was used with questions related to the characterization of the socio demographic and student profile. To assess well-being, the Andrews Faces Scale, WHO-5 Welfare Index was used and the Lifestyle Style questionnaire was used to evaluate the Lifestyle. It was obteined that 51.3% had a lifestyle classified as "good". None of the interviewees presented "Excellent" and "Need to improve" lifestyle. In the face scale 54.3% had a median well-being. And in the welfare scale, 40.6% presented low mood. It is concluded that a healthy lifestyle and satisfactory well-being contribute to the fact that undergraduates do not become future workers affected by some kind of alteration in their health.